INNOVATIVE SOLUTIONS IN THE LOGISTICS SYSTEM OF UZBEKISTAN AND THE DEVELOPMENT OF FOREIGN TRADE (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
The article analyzes the impact of innovative solutions in the logistics system of Uzbekistan and their effect on the development of foreign trade. It examines how the implementation of new technologies in Uzbekistan's transport infrastructure and logistics sector influences international trade and economic growth. The article discusses the innovations already implemented and expected changes, the modernization of the transport system, automation, and the reduction of logistics costs through digital systems. Additionally, it proposes the necessary measures to diversify Uzbekistan's foreign trade.